Relationship between falls and Fall Risk Increasing Drugs. A retrospective case control study. (30th September 2020) - Tiwana, N; Pietronigro, A; Mosillo, M; Principi, N; Carnevali, D; Avanzi, G M; Corna, S; Colombo, R; Castaldi, S
Abstract: Background: Falls and fall-related injuries are a major public health issue which needs global attention due to its clinical and socioeconomic impact. Inpatient falls are the most common adverse event in hospital. Important risk factors for falls are polypharmacy and the assumption of so-called Fall Risk Increasing Drugs (FRIDs). Aims of our study were to investigate the associations between falls and the use of medications among inpatients by conducting a retrospective case-control study in a rehabilitation hospital in Northern Italy in 2018. Methods: Three unique control for each faller, matched by age, sex and hospitalization ward, were selected. A Conditional Logistic Regression was performed to analyze the impact that 13 types of FRIDs individually and the number of administrated FRIDs had on the risk of falling. A second regression model was obtained adjusting the case-control matching for CIRS, Morse and Barthel scores. Results: We identified 148 cases and 444 controls. 3 types of FRIDs were significantly correlated (p < 0, 05) with an increased risk of falling: Antipsychotics [OR:1, 98;CI 95%:1, 01-3, 89], Antidepressants [OR:2, 18;CI 95%:1, 32-3, 59], Diuretics [OR:1, 71;CI 95%:1, 09-2, 68]. Antidepressants were the only type of FRID significantly correlated (p = 0, 008) even in the model adjusted for CIRS, Morse and Barthel scores [OR:2, 00;CI 95%:1, 20-3, 34]. The unadjusted model showed that the addition of one type of FRID to therapy was significantly associated with the fall event (p < 0.05) [OR:1.21;CI 95%: 1.05 - 1.40]. Conclusions: Assumption of drugs and polypharmacy could play a role in hospital falling. Recently developed fall risk assessment tools suffer from low specificity and sensitivity and do not assess these risk factors. A holistic approach with a multidimensional evaluation of the patient through screening tools, functional assessment tools and a full medical evaluation should be improved. Key messages: Drugs may represent an important variable in determining the risk of falls in hospitalized patients, but they should not be considered alone. Screening tools for fall risk should take into account polypharmacy such as other intrinsic and extrinsic risk factors within an holistic approach.